Acidified and ultrafiltered recovered coagulants from water treatment works sludge for removal of phosphorus from wastewater. (1st January 2016) - Keeley, James; Smith, Andrea D.; Judd, Simon J.; Jarvis, Peter
Abstract: This study used a range of treated water treatment works sludge options for the removal of phosphorus (P) from primary wastewater. These options included the application of ultrafiltration for recovery of the coagulant from the sludge. The treatment performance and whole life cost (WLC) of the various recovered coagulant (RC) configurations have been considered in relation to fresh ferric sulphate (FFS). Pre-treatment of the sludge with acid followed by removal of organic and particulate contaminants using a 2kD ultrafiltration membrane resulted in a reusable coagulant that closely matched the performance FFS. Unacidified RC showed 53% of the phosphorus removal efficiency of FFS, at a dose of 20 mg/L as Fe and a contact time of 90 min. A longer contact time of 8 h improved performance to 85% of FFS. P removal at the shorter contact time improved to 88% relative to FFS by pre-acidifying the sludge to pH 2, using an acid molar ratio of 5.2:1 mol H + :Fe. Analysis of the removal of P showed that rapid phosphate precipitation accounted for >65% of removal with FFS. However, for the acidified RC a slower adsorption mechanism dominated; this was accelerated at a lower pH. A cost-benefit analysis showed that relative to dosing FFS and disposing waterworks sludge to land, the 20 year WLC was halved by transporting acidified or unacidified sludge up to 80 km for reuse in wastewater treatment. A maximum inter-site distance was determined to be 240 km above the current disposal route at current prices. Further savings could be made if longer contact times were available to allow greater P removal with unacidified RC. Graphical abstract: Highlights: Purified water treatment works sludge was recovered as a coagulant. Ultrafiltered sludge achieved high levels of phosphorus removal. Clear differences in mechanism were identified for recovered and fresh coagulants. The importance of mixing and floc size was identified for recovered coagulants. Strategic implementation of recovered coagulant is needed to replace fresh coagulant.